Amino-functionalized MOF derived porous Fe3O4/N-doped C encapsulated within a graphene network by self-assembling for enhanced Li-ion storage. Issue 7 (11th May 2020) - Wang, Weijuan; Chen, Daming; Xu, Hui; Yu, Genxi; Sun, Shangqi; Zhang, Wei; Chen, Jian
Abstract : A graphene-wrapped porous Fe3 O4 /N-doped C composite was synthesized by an electrostatic interaction induced self-assembly process, showing an excellent electrochemical performance. Abstract : Fe3 O4 is regarded as one of the most promising anode materials for next generation lithium ion batteries. The main issues of the Fe3 O4 anodes are the severe pulverization and instability of the solid-electrolyte interphase (SEI) layer caused by the large volume change during the charge/discharge processes, as well as poor electrical conductivity. In this study, graphene-wrapped porous Fe3 O4 /N-doped C frameworks that were synthesized by a facial MOF-derived strategy coupled with an electrostatic interaction induced self-assembly process are reported for enhanced lithium ion storage. In the resulting architecture, integrating porous Fe3 O4 /N-doped C frameworks into graphene with an encapsulated structure effectively prevents the structural degradation and facilitates the formation of a stable SEI layer during the cycles. Moreover, benefiting from the highly conductive continuous graphene network and hierarchical porous structure, the electron conduction and lithium ion diffusion of the electrode are greatly enhanced. In virtue of the unique structure engineering, the as-built electrode exhibits high reversible capacity (764 mA h g −1 after 100 cycles at 0.2 A g −1 ), excellent rate capability (370 mA h g −1 at 8.0 A g −1 ) and enhanced cycling stability (441 mA h g −1 after 800 cycles at 2.0 A g −1 ).